Biological Properties of Milk-Derived Extracellular Vesicles and Their Physiological Functions in Infant - Jiang, Xue; You, Lianghui; Zhang, Zhenxing; Cui, Xianwei; Zhong, Hong; Sun, Xingzhen; Ji, Chenbo; Chi, Xia (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are released by all cells under pathological and physiological conditions. EVs harbor various biomolecules, including protein, lipid, noncoding RNA, messenger RNA, and DNA. In 2007, mRNA and microRNA (miRNA) carried by EVs were found to have regulatory functions in recipient cells. The biological function of EVs has since then increasingly drawn interest. Breast milk, as the most important nutritional source for infants, contains EVs in large quantities. An increasing number of studies have provided the basis for the hypothesis associated with information transmission between mothers and infants via breast milk-derived EVs. Most studies on milk-derived EVs currently focus on miRNAs. Milk-derived EVs contain diverse miRNAs, which remain stable both in vivo and in vitro; as such, they can be absorbed across different species. Further studies have confirmed that miRNAs derived from milk-derived EVs can resist the acidic environment and enzymatic hydrolysis of the digestive tract; moreover, they can be absorbed by intestinal cells in infants to perform physiological functions. miRNAs derived from milk EVs have been reported in the maturation of immune cells, regulation of immune response, formation of neuronal synapses, and development of metabolic diseases such as obesity and diabetes. This article reviews current status and advances in milk-derived EVs, including their history, biogenesis, molecular contents, and biological functions. The effects of milk-derived EVs on growth and development in both infants and adults were emphasized. Finally, the potential application and future challenges of milk-derived EVs were discussed, providing comprehensive understanding and new insight into milk-derived EVs.